2019
DOI: 10.3390/coatings9100633
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene Glycol Functionalized Gadolinium Oxide Nanoparticles as a Potential Electrochemical Sensing Platform for Hydrazine and p-Nitrophenol

Abstract: The current work reports the successful synthesis of ethylene glycol functionalized gadolinium oxide nanoparticles (Gd2O3 Nps) as a proficient electrocatalytic material for the detection of hydrazine and p-nitrophenol. A facile hydrothermal approach was used for the controlled growth of Gd2O3 Nps in the presence of ethylene glycol (EG) as a structure-controlling and hydrophilic coating source. The prepared material was characterized by several techniques in order to examine the structural, morphological, optic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 55 publications
(59 reference statements)
0
8
0
Order By: Relevance
“…Further, the absorbance of UV–vis spectra at 400 nm versus p -NP concentration from 6.67 to 600 μM showed a satisfactory linear relationship ( R 2 = 0.996) with a colorimetric LOD of 4.97 μM for p -NP (Figure G,H). The comparison of the proposed sensing strategy with previous methods for the detection of p -NP is summarized in Table , which compares the sensitivity of response between CTAB-Cu NPs and p -NP.…”
Section: Resultsmentioning
confidence: 99%
“…Further, the absorbance of UV–vis spectra at 400 nm versus p -NP concentration from 6.67 to 600 μM showed a satisfactory linear relationship ( R 2 = 0.996) with a colorimetric LOD of 4.97 μM for p -NP (Figure G,H). The comparison of the proposed sensing strategy with previous methods for the detection of p -NP is summarized in Table , which compares the sensitivity of response between CTAB-Cu NPs and p -NP.…”
Section: Resultsmentioning
confidence: 99%
“…Chaudhary S. et al [64] reported the synthesis and characterization of Gd 2 O 3 NPs functionalized with ethylene glycol (EG) by the hydrothermal method starting from GdCl 3 and EG. A variation on GdCl 3 concentration was done from 5 mM to 25 mM to study the effects of synthetic parameters over the optical, photoluminescence, and band-gap variation.…”
Section: Hydrothermal Methodsmentioning
confidence: 99%
“…Chaudhary S. et al [64] reported the synthesis and Gd 2 O 3 NPs functionalized with ethylene glycol (EG) by the hydrothermal method starting from GdCl 3 and EG. (See Section 3.1.5 for more details).…”
Section: Functionalization By Non-covalent Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…These materials exhibited a high surface area and uniformity of unique mesoporous particle morphology, generating many active sites, a fast-ionic transport and enhanced capacitive properties. Chaudhary et al [10] also used a hydrothermal approach for the controlled growth of gadolinium oxide (Gd 2 O 3 ) nanoparticles in the presence of ethylene glycol (EG) as a structure-controlling and hydrophilic coating source. The structural, optical, photoluminescence, and sensing properties of the prepared materials, as well as their thermal stability, resistance toward corrosion, and decreased tendency toward photobleaching made Gd 2 O 3 a good candidate for the electrochemical sensing of p-nitrophenol and hydrazine using voltammetric and amperometric techniques.…”
Section: This Special Issuementioning
confidence: 99%